2021
DOI: 10.1111/imj.15190
|View full text |Cite
|
Sign up to set email alerts
|

Managing COVID‐19 in patients with inflammatory bowel disease: navigating unprecedented challenges

Abstract: The COVID‐19 pandemic has demanded a rapid adaptation in healthcare provision, including patients with inflammatory bowel disease (IBD). This viewpoint discusses some of the unique challenges in managing comorbid IBD and COVID‐10 experienced by our team at The Royal Melbourne Hospital, which was at the epicentre of the COVID‐19 ‘second‐wave’ surge in Melbourne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A meta-analysis considering 96,852 patients reported that the use of corticosteroids increased the mortality of patients with COVID-19 [270], which could be due to the early use of corticosteroids facilitating the viral replication of SARS-CoV-2 due to low immune resistance, leading to an increase in viral load. Therefore, the WHO only recommends their use in critically ill COVID-19 patients at 7 days after the first symptom [271,272]. Hence, the use of this drug will depend on the timing and characteristics of each patient, in order to obtain a positive prognosis.…”
Section: Criteria To Consider For Corticosteroidsmentioning
confidence: 99%
“…A meta-analysis considering 96,852 patients reported that the use of corticosteroids increased the mortality of patients with COVID-19 [270], which could be due to the early use of corticosteroids facilitating the viral replication of SARS-CoV-2 due to low immune resistance, leading to an increase in viral load. Therefore, the WHO only recommends their use in critically ill COVID-19 patients at 7 days after the first symptom [271,272]. Hence, the use of this drug will depend on the timing and characteristics of each patient, in order to obtain a positive prognosis.…”
Section: Criteria To Consider For Corticosteroidsmentioning
confidence: 99%
“…Although these, and in particular dexamethasone, are used in the treatment of severe forms of infection associated with respiratory distress [ 69 ], their use must be reserved for the second phase of the disease, when the damage mediated by the hyper-inflammatory state prevails. On the contrary, they could increase replication and viral load if used immediately [ 70 , 71 ]. It has been demonstrated that the chronic use of systemic corticosteroids leads to immunosuppression.…”
Section: Drugs and Inflammatory Bowel Diseases: What Have We Learned?mentioning
confidence: 99%
“…At the beginning of the pandemic, the use of corticosteroids was considered controversial, although Randomized Evaluation of COVID-19 Therapy (RECOVERY) trial provided evidence that dexamethasone 6 mg once daily for 10 days reduced mortality in COVID-19 patients receiving oxygen therapy [16]. Some investigators noted that early corticosteroid use might lead to increased virus replication and thus higher viral loads [25]. Meanwhile, there is an analysis suggesting that the initiation of treatment in the second week of symptom onset, when the immunopathological phenomenon dominates, may be beneficial [16].…”
Section: Introductionmentioning
confidence: 99%